Analisis Faktor Penyebab Kemiskinan Di Kabupaten Dompu (2011-2021) - Rizqiah, Pelita; Jufri, Akhmad; Yuniarti, Titi (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2024)
This research aims to find out whether Economic Growth, Human Development Index, Unemployment Rate influence poverty in Dompu Regency. This research uses secondary data and is a quantitative type of research. The location of this research is Dompu Regency, West Nusa Tenggara. The data collection technique uses documentation based on data obtained by the Central Statistics Agency (BPS) of Dompu Regency. The data analysis method used is multiple linear regression. From the results of research regarding the analysis of factors causing poverty in Dompu Regency, it can be concluded that economic growth is negative and not significant to poverty, while the Human Development Index (HDI) is negative and significant to poverty, and the unemployment rate is negative and not significant to poverty